EPIDEMIOLOGY OF DERMATITIS IN FARMERS - Yarmaliza Yarmaliza; Teungku Nih Farisni; Fitriani Fitriani; Veni Nella Syahputri; Zakiyuddin Zakiyuddin; Fitrah Reynaldi (Jurnal Berkala Epidemiologi, 2020)
Background: Dermatitis refers to the inflammation of the skin and can be acute, sub-acute, or chronic. In 2014, there were 364 cases in Meureubo Health Center, which increased sharply to 1,854 cases in 2915 and 2,794 cases in 2016. Purpose: This study looks at the relationship between personal hygiene and a history of contact with families suffering from dermatitis and the incidence of dermatitis in farmers in West Aceh District. Methods: This research was conducted using a descriptive observational design and was carried out in the working area of the Meureubo Public Health Center (Puskesmas Meureubo) in West Aceh Regency between 5 December 2017 and 8 January 2018. A purposive sampling technique was used for the collection of primary and secondary data. Results: The majority of respondents were male (60%), aged 31–40 years (66%), and had a low education level (76%). The majority of farmers had poor personal hygiene (61%) and had a history of contact with families suffering from dermatitis (66%). Conclusion: There is a high prevalence of poor personal hygiene in farmers, and they tend to have a history of contact with family members suffering from dermatitis.